Ancaman Hacker Dan Cybercrime Di Indonesia Dan Pentingnya Pemahaman Untuk Keamanan Akun Media Sosial Instagram Pada Kalangan Mahasiswa - Kurnianto, Aji; Wijaya, Alfa Reno; Assyafii, Adilillah (Journal of Student Development Information System (JoSDIS), 2026)
The development of digital technology has increased social media usage among university students, but has also been accompanied by an increase in the threat of hackers and cybercrime. Low awareness of account security has led to many users becoming victims of hacking and personal data theft, particularly on the Instagram platform. This study aims to analyze cybercrime threats in Indonesia and the importance of understanding social media account security for university students. The method used was qualitative descriptive analysis through a review of recent literature. The results indicate that the main factor contributing to user vulnerability lies in a lack of digital literacy and understanding of basic security practices, such as the use of strong passwords and dual authentication. Therefore, increased cybersecurity education on campus is needed to make students more vigilant, responsible, and capable of protecting their personal data in the digital world.